ARFI elastography of the omentum: feasibility and diagnostic performance in differentiating benign from malignant omental masses - Amjad Alhyari; Christian Görg; Christoph Frank Dietrich; Corrina Trenker; Lena Strauch; Ehsan Safai Zadeh (BMJ Open Gastroenterology, 2022)
Objective To evaluate the feasibility and diagnostic performance of acoustic radiation force impulse (ARFI) elastography in different omental masses (OM).Design This was a retrospective analysis of 106 patients with OM defined as omental thickness ≥1 cm, who underwent abdominal B-mode ultrasound (US) and standardised ARFI examinations of the OM between September 2018 and June 2021 at our university hospital. A cytohistological confirmation was available in 91/106 (85.8%) of all OM, including all 65/65 (100%) malignant OM (mOM) and 26/41 (63.4%) of benign OM (bOM). In 15/41 (36.6%) of bOM; cross-sectional imaging and or US follow-up with a mean duration of 19.8±3.1 months was performed. To examine the mean ARFI velocities (MAV) for potential cut-off values between bOM and mOM a receiver operating characteristic analysis was implemented.Results The MAV in the mOM group (2.71±1.04 m/s) was significantly higher than that of bOM group (1.27±0.87 m/s) (p<0.001). Using 1.97 m/s as a cut-off yielded a sensitivity and specificity of 76.9% and 85.4%, respectively, in diagnosing mOM (area under the curve=0.851, 95% CI=0.774 to 0.928).Conclusion ARFI elastography is feasible in the omentum and may represent a good non-invasive additional tool in differentiating bOM from mOM.